2019
DOI: 10.1289/ehp5057
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels and Risk of Atherosclerosis in the Carotid Artery: Results from a Swedish Cohort

Abstract: BACKGROUND: Lead exposure has been associated with increased incidence of adverse clinical cardiovascular outcomes. Atherosclerosis has been suggested as one of the underlying mechanisms, and findings from experimental studies support this, but human data are scarce. OBJECTIVES: Our objective was to determine the association between environmental lead exposure based on blood lead (B-Pb) concentrations and the prevalence of atherosclerotic plaque in the carotid artery. METHODS: We used cross-sectional data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…1988 ). A recent study reported an association between BLL and atherosclerotic plaque in the carotid artery ( Harari et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…1988 ). A recent study reported an association between BLL and atherosclerotic plaque in the carotid artery ( Harari et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid plaque rupture and thrombus formation are the main causes of ischemic stroke. Patients with unstable/vulnerable plaque AS (UA) are prone to rupture and thrombus formation, leading to cardiovascular or cerebrovascular events, such as acute coronary syndrome, ischemic stroke, and peripheral vascular disease ( 2 ). Therefore, identifying the properties of carotid plaques may help improve the prediction and prevention of cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…An association between lead and cardiovascular disease has been recognized and considered an established risk factor for oxidative stress, inflammation, and the triggering event of atherosclerosis [67].…”
Section: Heavy Metalsmentioning
confidence: 99%